Diseño y construcción de un banco de automatización Industrial con tecnología de bus de campo FIELDBUS FOUNDATION. - Calderón Paladines, Holger Bolívar (2009)
The automation of manufacturing processes is a specialty that is increasingly gaining followers who want to develop research projects, technical and engineering in which they can use the new techniques of measurement, monitoring and control elements of which include auto, electrical, computer , Electricity, communications and instrumentation industry, among others. With this work we want to show the whole process of design, construction, assembly, programming, and setting up a bank with a technology Automatización Fieldbus Foundation (FF) that allows the Faculty of Electrical from the National University of Loja introduced practical way in knowledge and development of these advanced technologies not very common in schools and university if very much present in current industrial processes. Students and teachers now have the opportunity to learn about this technology through a concrete example in which the report describes all the steps in obtaining this bank. This first job will encourage all those with a preference for This specialty of the race itself of Electrical Engineering taught at other universities in the country.